2010
DOI: 10.2214/ajr.09.2897
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pulmonary Circulation Parameters Using Time-Resolved MR Angiography in Patients After Ross Procedure

Abstract: Patients after undergoing the Ross procedure had prolonged pulmonary transit times compared with normal control patients; this and other pulmonary circulation parameters best correlate with worsened right ventricular ejection fraction and may be predictors of right ventricular dysfunction in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
15
1
Order By: Relevance
“…It has been suggested that an increase in pulmonary blood volume is the main reason for vascular remodeling and resultant pulmonary hypertension during chronic hypoxia (19). Such increases have also been found to be correlated with measures of RV dysfunction such as lower ejection fraction and ventricular dilation (17). The result of our study shows the arterial blood volume in patients with PAH is significantly higher than controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an increase in pulmonary blood volume is the main reason for vascular remodeling and resultant pulmonary hypertension during chronic hypoxia (19). Such increases have also been found to be correlated with measures of RV dysfunction such as lower ejection fraction and ventricular dilation (17). The result of our study shows the arterial blood volume in patients with PAH is significantly higher than controls.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Dynamic contrast-enhanced (DCE) time-resolved magnetic resonance (MR) imaging is a technique whereby an intravenous contrast bolus can be tracked through the cardiopulmonary vascular system in three dimensions with time. [5][6][7][8][9][10][11][12] Several previous studies have assessed DCE-MR in patients with pulmonary hypertension, 8,9,[13][14][15] and significant correlations have been identified between timeresolved DCE-MR angiography and invasive prognostic indicators. However, the role of DCE-MR pulmonary vascular transit time (TT) measurements as prognostic markers in PAH has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…1). In normal subjects, this is about 6.8 ± 1.7 s [6]. In patients with pulmonary hypertension or congestive heart failure (CHF), pulmonary circulation can be slow and PTT will be prolonged, which may lead to delayed contrast arrival in the non target vessel, e.g.…”
Section: Normal Circulationmentioning
confidence: 99%